Liberia : Seventh Review Under the Extended Credit Facility Arrangement. (IMF Staff Country Reports; Country Report, 2011)
The Executive Board of the IMF has completed the seventh review of Liberia's economic program under the Extended Credit Facility (ECF). The completion of the review enables the disbursement of SDR 4.44 million, which will bring total disbursements under the arrangement to SDR 243.5 million. The ECF arrangement for Liberia was initially approved in March 2008, for an amount of SDR 239.02 million. In June 2010, Liberia reached the Heavily Indebted Poor Countries Initiative Completion Point and received debt relief equivalent to more than 90 percent of debt outstanding.